Algal Flora in some Springs of Shawre Valley, Ranya, Kurdistan Region – Iraq - Ahmed, Alwan Qader; Yaseen, Sara Abdulkhaleq; Aljoborey, Abdulmunem Dherar Abdullah (Iraqi Journal of Science, 2025)
This study aims to assess the diversity of algal flora from some spring water in Shawre Valley. The non-diatom algal composition of four selected spring sites studied was situated at Shawre Valley within Ranya district Sulaymaniyah governorate every month from September 2022 to April 2023. A total of 79 algal species were identified from 6 divisions. The majority of them belong to Chlorophyta, with 35 species (44.30%), followed by Cyanophyta, with 32 species (40.51%) Euglenophyta with 5 species (6.33%), Xanthophyta with 4 species occupied (5.06%), Rhodophyta with 2 species (2.53%) and Charophyta with only one species occupied (1.26%). The most representative genus was Oscillatoria, with 6 taxa identified, each of Calothrix and Oedogonium with 4 species, Merismopedia, Scenedesmus, Ulothrix, Spirogyra, Cosmarium and Tribonema with 3 species were dominant.